Analysis and investigation of the leakage failure of a casing used in a shale gas well. (January 2022) - Tong, Ke; Zhao, Jin-lan; Liu, Qiang; Zhu, Bo; Jin, Quan; Qu, Ting-ting; Liu, Qing; Cong, Shen
Highlights: Reported a rare casing leakage failure in a shale gas well in western China during pressure testing. Failure analysis of the casing and investigation of the manufacturing plant revealed that during the steel pipe rolling process, the bolts on the balance cylinder of the continuous pipe mill dropped onto the pipe. The bolt acts as a dissimilar metal substance to destroy the continuity of the metal. The FEA calculation results show that when the casing is used in the field, under axial tension and internal pressure, the equivalent force at the defect is much greater than the yield strength of the casing. Therefore, the crack at the defect quickly propagated and penetrated the entire wall thickness of the casing, resulting in the final failure of the casing. In order to avoid the recurrence of such failure accidents, rectification suggestions were put forward. Abstract: A casing leaked in a shale gas well during pressure testing. A series of experiments including macroscopic observation, non-destructive inspection, physical and chemical inspection, optical microscope, scanning electron microscope (SEM) and energy dispersive spectrometry techniques (EDS) were carried out to analyze the failure accident. The finite simulation analysis (FEA) method was used to analyze the effect of internal pressure on the defective parts of the casing. Based on the experiment result and manufacturing process investigation, the root cause was obtained. During the casing pipe rolling process, the bolts of size M12 × 60 mm on the balance cylinder of the continuous pipe mill were loosened and dropped onto the pipe. Under the dual action of the roller and the mandrel, the bolts are 'inlaid' inside the casing as a dissimilar metal substance. The bolt head almost occupies the entire wall thickness of the casing, resulting in the remaining wall thickness of the casing being less than 1 mm. The dissimilar metal inside the casing destroys the continuity of the pipe and severely reduces the pressure bearing capacity of the casing. The FEA calculation results show that the equivalent stress at the defect is lower than the yield strength of the pipe body during the factory hydraulic test. While, in the field pressure test, the equivalent stress at the defect is far greater than the yield strength of the casing under the action of axial tension and internal pressure. Therefore, the crack at the defect quickly propagated and penetrated the entire wall thickness of the casing, resulting in leakage. In order to avoid similar accidents, suggestions to prevent such failures are proposed.